1997
DOI: 10.1055/s-2007-994333
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Cord Entanglements and Gestational Age

Abstract: The purpose of this observational study was to investigate the relation between nuchal cord entanglements and gestational age. Computerized data from our hospital perinatal database were reviewed between January 1990 and December 1994. Data from all deliveries > or = 20 weeks' gestation underwent either a Cochran-Mantel test for trend or Chi-square testing where appropriate. Of the 13,895 singleton deliveries, the finding of an entanglement increased significantly from 5.8% at 20 weeks to 29.0% at 42 weeks' ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 1 publication
2
50
1
2
Order By: Relevance
“…Begum et al [5] in their series had no perinatal mortality with nuchal cord which is similar to observation of Larson et al [9] and Miser [10] which does not correspond to our study.…”
Section: Discussionsupporting
confidence: 67%
“…Begum et al [5] in their series had no perinatal mortality with nuchal cord which is similar to observation of Larson et al [9] and Miser [10] which does not correspond to our study.…”
Section: Discussionsupporting
confidence: 67%
“…Th ese studies generally support that nuchal cord is a common fi nding in fetal life, with decreasing rates in the newborn (1, 2, 5, 6). However, rather than showing decreasing rates, one study showed that nuchal cord rates increased linearly from 6% in the 20th gestational week to 29% in the 42nd gestational week, regardless of whether the entanglement involved a single loop or multiple loops (3).…”
Section: Discussionmentioning
confidence: 99%
“…Th e Table lists studies related to the incidence of nuchal cord and two case reports with fetal demise due to nuchal cord (1)(2)(3)(4)(5)(6)(7)(8). Th e reported incidence of nuchal cord varies, with the highest rates of 43% in the 13th to 16th gestational week and 8.3% in newborns (1,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations